A novel ferritin subunit gene from Asian green mussel, Perna viridis (Linnaeus, 1758). Issue 115 (August 2021) - Sumithra, T.G.; Neethu, B.R.; Reshma, K.J.; Anusree, V.N.; Reynold, P.; Sanil, N.K.
Abstract: Iron sequestration through ferritin forms a major part of innate immune response in molluscs and detailed understanding of ferritin gene and its functions can be directly applied in infection and disease management studies. Accordingly, identification and detailed molecular characterization of a ferritin subunit gene from a commercially significant marine mussel Perna viridis was targeted. Molecular screening using degenerate primers in total mantle RNA resulted in the amplification of a novel ferritin gene fragment having <87% identity to the reported ferritin gene sequences. Rapid amplification of cDNA ends-PCR was followed to generate complete cDNA sequence of P. viridis ferritin (PvFer). The complete cDNA was found to be 798 bp, containing an open reading frame of 522 bp, 5′ untranslated region (UTR) of 112 bp and 3′ UTR of 165 bp. The 5′ UTR and 3′ UTR were shown to contain an iron response element (IRE) and a polyadenylation signal (767AATAAA772) with poly (A) tail, respectively. Prediction of stem loop structure revealed that, PvFer-IRE can be folded into a typical secondary stem loop structure, having 5-CAGUGA-3' loop, proximal stem of five paired bases followed by a bulged cysteine, and six nucleotide bottom stem, indicating that expression of PvFer is regulated by iron at the translational level. ORF was found to encode 175 amino acid protein with calculated molecular mass of 19.97 kDa and isoelectric point of 4.97. Examination for signal peptide and phylogenetic analysis confirmed that PvFer belonged to cytosolic ferritins of molluscs. Conserved domain analysis showed that PvFer contained both ferroxidase diiron center and ferrihydrite nucleation center, analogous to ferritin M subunit of bony fishes and amphibians. However, amino acid sequence and glycosylation site showed more homology to vertebrate ferritin H subunits. Predicted 3D models of PvFer resembled the typical spatial features of ferritin proteins. The study forms the first comprehensive identification of a ferritin subunit gene in a true/common mussel (Order: Mytilida). Further, the detailed molecular phylogeny conducted through the present study revealed certain thought provoking insights on ferritin genes of the phylum Mollusca. Highlights: First report of full coding sequence features of ferritin subunit from Mytilida. Showed <87% identity to the reported incomplete ferritin sequences of Mytilida. The putative protein (PvFer) belonged to cytosolic ferritins of molluscs. PvFer was shown to contain ferroxidase diiron and ferrihydrite nucleation centers.